Analysis Of The Success Of Corporate Social Responsibility Activities At PT Ecogreen Oleochemicals Batam - Nabila Sari; Alldila Nadhira Ayu Setyaning (SEAN Institute, 2024)
This study aims to evaluate and analyze the success of the Corporate Social Responsibility (CSR) program